Inorganic Synthesis Based on Reactions of Ionic Liquids and Deep Eutectic Solvents - Zhang, Tao; Doert, Thomas; Wang, Hui; Zhang, Suojiang; Ruck, Michael (Angewandte Chemie International Edition, 2021)
Ionic liquids and deep eutectic solvents are of growing interest as solvents for the resource-efficient synthesis of inorganic materials. This Review covers chemical reactions of various deep eutectic solvents and types of ionic liquids, including metal-containing ionic liquids, [BF4]−- or [PF6]−-based ionic liquids, basic ionic liquids, and chalcogen-containing ionic liquids. Cases in which cations, anions, or both are incorporated into the final products are also included. The purpose of this Review is to raise caution about the chemical reactivity of ionic liquids and deep eutectic solvents and to establish a guide for their proper use.
CRIS-Team Scopus Importer:2022-04-14
Keywords: chemical reactivity; deep eutectic solvents; inorganic materials; ionic liquids; ionothermal synthesis